Complement protein levels in plasma astrocyte‐derived exosomes are abnormal in conversion from mild cognitive impairment to Alzheimer's disease dementia. Issue 1 (14th December 2018) - Winston, Charisse N.; Goetzl, Edward J.; Schwartz, Janice B.; Elahi, Fanny M.; Rissman, Robert A.
Abstract: Introduction: Levels of complement proteins (CPs) in plasma astrocyte‐derived exosomes (ADEs) that are abnormal in Alzheimer's disease (AD) have not been assessed in mild cognitive impairment (MCI). Methods: Participants (n = 20 per group) had either MCI converting to dementia within 3 years (MCIC), MCI remaining stable over 3 years (MCIS), Alzheimer's disease, or were controls. CPs of ADEs isolated from plasmas by anti‐human glutamine aspartate transporter antibody absorption were quantified by ELISAs. Results: ADE levels of C1q and C4b of the classical pathway, factor D and fragment Bb of the alternative pathway, and C5b, C3b, and C5b‐C9 of both pathways were significantly higher in patients with MCIC than those with MCIS. ADE levels of inhibitory CPs decay‐accelerating factor, CD46, CD59, and type 1 complement receptor were significantly lower in patients with MCIC than those with MCIS. Discussion: ADE CPs are components of neurotoxic neuroinflammation that may be predictive biomarkers of MCI conversion to Alzheimer's disease.